2014
DOI: 10.35663/amp.2014.314.187
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de burnout en internos de medicina: un problema urgente

Abstract: Síndrome de burnout en internos de medicina: un problema urgente

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2019, the World Health Organization reported that up to 75% of the Mexican population experiences high levels of work-related stress. This can lead to the development of burnout syndrome [ 36 ], which has been associated with high-stress occupations, caregiving occupations, and jobs with long working hours [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the World Health Organization reported that up to 75% of the Mexican population experiences high levels of work-related stress. This can lead to the development of burnout syndrome [ 36 ], which has been associated with high-stress occupations, caregiving occupations, and jobs with long working hours [ 37 ].…”
Section: Discussionmentioning
confidence: 99%